Arsenic in permafrost-affected rivers and lakes of Tibetan Plateau, China. Issue 1 (1st January 2019) - Yu, Congrong; Sun, Yufeng; Zhong, Xiaoyan; Yu, Zhongbo; Li, Xiangying; Yi, Peng; Jin, Huijun; Luo, Dongliang
ABSTRACT: With the climate warming leading to thawing permafrost, the trace metal releasing from the permafrost is of increasing importance. The source area of the Yellow river (SAYR) in Tibet Plateau, underlain by permafrost which provides important source water, was investigated. One hundred and eleven water samples across SAYR were collected in April 2014, when permafrost thawing began and the precipitation season had not arrived yet. It was found that the arsenic concentration level was relatively higher than other pristine surface water in the world, but similar to other source regions on the Tibetan Plateau, showing SAYR is pristine and can serve as a reference region for determining the human influence on permafrost-affected landscapes. The positive correlation of arsenic with sulfate suggested that the arsenic was predominantly derived from the weathering process of arsenic-rich sulfides. Climate warming enhanced thawing depth of permafrost may accelerate the release and mobilization of arsenic to the surface water.